2007
DOI: 10.1111/j.1471-4159.2007.05207.x
|View full text |Cite
|
Sign up to set email alerts
|

Social isolation rearing‐induced impairment of the hippocampal neurogenesis is associated with deficits in spatial memory and emotion‐related behaviors in juvenile mice

Abstract: Experiences during brain development may influence the pathogenesis of developmental disorders. Thus, social isolation (SI) rearing after weaning is a useful animal model for studying the pathological mechanisms of such psychiatric diseases. In this study, we examined the effect of SI on neurogenesis in the hippocampal dentate gyrus (DG) relating to memory and emotion-related behaviors. When newly divided cells were labeled with 5-bromo-2'-deoxyuridine (BrdU) before SI, the number of BrdU-positive cells and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
176
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 223 publications
(183 citation statements)
references
References 56 publications
7
176
0
Order By: Relevance
“…Lin et al (13) have reported that NPAS4 regulates the development of GABAergic inhibitory synapses in an activity-dependent manner and suggested its homeostatic role in the balance between excitatory and inhibitory neuronal activities in the brain. We previously reported that reduced Npas4 mRNA levels may contribute to impairments in adult neurogenesis in the hippocampus, memory and emotional behaviors induced by social isolation or restriction stress (16,17). Recent studies (18,19) revealed that NPAS4 is important in memory formation and consolidation.…”
mentioning
confidence: 99%
“…Lin et al (13) have reported that NPAS4 regulates the development of GABAergic inhibitory synapses in an activity-dependent manner and suggested its homeostatic role in the balance between excitatory and inhibitory neuronal activities in the brain. We previously reported that reduced Npas4 mRNA levels may contribute to impairments in adult neurogenesis in the hippocampus, memory and emotional behaviors induced by social isolation or restriction stress (16,17). Recent studies (18,19) revealed that NPAS4 is important in memory formation and consolidation.…”
mentioning
confidence: 99%
“…At a cellular level, EE triggers an increase in the generation and integration of adult-born neurons into the granule cell layer (GCL) of the hippocampus and increases dendritic branching complexity and synapse formation in excitatory neurons of the hippocampus (Kempermann et al 1997(Kempermann et al , 1998van Praag et al 2000;Faherty et al 2003). Further, reduced sensory stimulation leads to a decrease in progenitor proliferation and dendrite branch patterns, which likely results in the wellcharacterized increase in depression and reduced cognitive capacity (Silva-Gomez et al 2003;Bianchi et al 2006;Ibi et al 2008). Importantly, retrospective analysis of humans exposed to psychosocial or behavioral enrichment appears to support the findings of animal studies (Cotman and Berchtold 2002;Agrigoroaei and Lachman 2011;Erickson et al 2011).…”
mentioning
confidence: 99%
“…[11][12][13][14][15][16] Generally, SI stress impairs neuronal precursor cells at multiple steps, including the mitotic and survival phases of neurogenesis. 17 SI also suppresses the expression of glutamate receptor, 18 which functions in learning and memory. 19 In contrast, SI-induced abnormalities can be rescued by environmental enrichment, 14 and fluoxetine, an antidepressant that selectively inhibits serotonin re-uptake.…”
Section: Introductionmentioning
confidence: 99%
“…19 In contrast, SI-induced abnormalities can be rescued by environmental enrichment, 14 and fluoxetine, an antidepressant that selectively inhibits serotonin re-uptake. 17,20 Interestingly, environmental enrichment ameliorates SIinduced defects at both the mitotic and post-mitotic phases of hippocampal neurogenesis, 21 whereas fluoxetine mainly protects against the SI-induced downregulation of cell proliferation. 17 To investigate the physiological roles of L1-RTP in the CNS, we first examined L1 copy numbers in the hippocampus genome of mice at different ages.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation